A capabilities driven model for web services description and composition. (2016) - Baccar, Sana; Rouached, Mohsen; Abid, Mohamed
Service-oriented architectures (SOA) foster the integration of different technologies and platforms coming from various enterprises, and bring a new level of flexible modularity that is able to guarantee end-to-end quality of service. However, a current bottleneck in the current process of modelling compositions in SOA is the expert level needed in order to achieve such a composition. This is mainly due to the imperative programming paradigm they are based on. A language such as BPEL is clearly an expert language, and specifying and programming a composition using BPEL is a lengthy, costly, and high risk process. To overcome this limitation, we propose in this paper to use a declarative approach to model services and services compositions. This approach relies on a capabilities service specification, powered by reasoning techniques to handle both functional and non-functional requirements and highly expressive interaction models without over-specifying them. It enables to support flexible and self-managed compositions that are able to adapt to changes that may happen continuously and unpredictably.